Exploring ChatGPT as a Virtual Assistant for Personalized Writing Experience: EFL Students’ Insights (Architecture Image Studies, 2025)
Despite the growing adoption of ChatGPT in language learning, there is a lack of research examining EFL students’ perceptions of its usefulness, ease of use, and overall impact—particularly in relation to variables such as gender and usage duration within the Saudi educational context. This study explores how EFL students view ChatGPT as a virtual assistant for personalized writing experiences. It assesses the app's usefulness, support, and usability, as well as how these opinions differ by gender and usage frequency. Using a descriptive-inferential design, data were collected from 140 students through a questionnaire, followed by semi-structured interviews with 20 participants. Quantitative results show moderate perceptions, with longer users (7–9 months) and females reporting considerably more positive opinions than shorter users (0–3 months) and males. Regarding qualitative insights, ChatGPT is seen as helping to improve grammar, vocabulary, and confidence when writing emails, essays, and research assignments. However, they also point to obstacles such as restricted access, language barriers, inadequate internet, and concerns about over-reliance. These results reveal that ChatGPT enhances writing abilities, yet its ethical and practical limits must be addressed by guided integration. The findings have implications for EFL pedagogy, highlighting the importance of careful monitoring and targeted training to ensure the effective integration of AI tools.